2006
DOI: 10.1177/0146167205279582
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Enacted Social Support Associated With Increased Distress? Using Simulation to Test Two Possible Sources of Spuriousness

Abstract: Although perceiving that social support is available is often associated with psychological benefits in times of stress, there is evidence that actually receiving support is associated with increased distress. To assess whether this latter association could be spurious, the authors conducted computer simulation studies to examine two theoretical models that could give rise to it. Study 1 examined a process whereby distress leads to provision of support rather than the reverse. Study 2 examined a process whereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 31 publications
1
61
1
Order By: Relevance
“…Besides this, our research indicated crucial age differences: Among older individuals negative effects of received social support may be no longer evident which is in line with SST assuming a social network constellation with more emotionally meaningful interaction partners (Carstensen et al 1999). Importantly, these findings also held when controlling for previous-day NA, implying that received emotional support was not just a reaction of the social network to a higher level of NA in the younger participants (''reverse causation,' ' Seidman et al 2006). Those findings have several conceptual implications for current models of socio-cognitive aging.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Besides this, our research indicated crucial age differences: Among older individuals negative effects of received social support may be no longer evident which is in line with SST assuming a social network constellation with more emotionally meaningful interaction partners (Carstensen et al 1999). Importantly, these findings also held when controlling for previous-day NA, implying that received emotional support was not just a reaction of the social network to a higher level of NA in the younger participants (''reverse causation,' ' Seidman et al 2006). Those findings have several conceptual implications for current models of socio-cognitive aging.…”
Section: Discussionsupporting
confidence: 78%
“…Taking changes across time into account is especially important, because one potential mechanism for the negative associations between received social support and well-being is ''reverse causation.'' This means that people with lower well-being receive more social support (Seidman et al 2006). This study applied a daily-diary design to control for the possibility of reverse causation and to investigate possible short-term reactions to receipt of support.…”
Section: Age Differences Of Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, by demonstrating the effects in both highly stressed individuals (ex-aminees) and less stressed individuals (partners), we feel confident that support receipt can have these mixed effects regardless of overall stress level. Furthermore, the simulation study by Seidman et al (2006) concluded that the negative effects associated with support receipt in naturalistic studies could not reasonably be caused by co-occurring negative events-the parameter values needed for such an association were unrealistic. Finally, a recent experimental study demonstrated the negative effects of support receipt on mood (Bolger & Amarel, 2007).…”
Section: Limitationsmentioning
confidence: 99%